A capacity-aware MIMO-beamforming approach for cognitive radio enabled smart grid systems. (2016) - Hefnawi, Mostafa
This paper proposes an adaptive multiple input multiple output-beamforming scheme (MIMO-BF) for cognitive radio enabled broad band smart grid (SG) systems concurrently sharing the same spectrum with the primary network (PN) and employing orthogonal frequency-division multiplexing with space division multiple access (OFDM-SDMA) technologies. The proposed algorithm uses gradient search of the channel capacity to seek, iteratively, the optimal transmit weight vectors that maximise the MIMO channel capacity for each cognitive user of the SG network, while controlling the interference levels to the PN. We evaluate the symbol error rate (SER) and system capacity performances of the proposed cognitive OFDM-SDMA system and show by simulation that they outperform cognitive systems based on opportunistic approaches. It is also shown that when the SG system is using the proposed schemes it has better control on the interference at the primary base station than the one based on opportunistic capacity-aware.